EFFECTS OF CONCEPT MAPS ON STUDENTS CRITICAL THINKING SKILLS IN SCIENCE EDUCATION - (:unkn) unknown (SCIBULCOM LTD, 2013)
This study aims to investigate the effects of creating concept maps by using paper and pencil on primary school students critical thinking skills in science education. Experimental research model was used with pre- and post-test control group design. The participants of the study were 60 6th graders (ages 11-12) at a primary school, which was randomly chosen among the public primary schools in Uskudar, Istanbul, during the 2011-2012 school period. The experimental group and the control group were designated objectively among the student groups that have similar characteristics. Implementation period had lasted for 20 class hours in total. The reliability coefficient of the critical thinking skills scale (the Cronbach alpha) was 0.87. It was seen that there were significant differences between the critical thinking scores of the students who created their concept maps by using paper and pencil and those of the students who were instructed not to create the concept maps. Thus, it could be said that creating the concept maps enables the students to develop their critical thinking skills in science education.
Keywords: constructivist educational environments; science education; concept maps; critical thinking; active learning; NURSING-STUDENTS; KNOWLEDGE